Suplementação mineral injetável (fosfosal®) em fêmeas suínas sobre parâmetros reprodutivos e desempenho produtivo dos leitões na maternidade - Vasconcelos, Deborah Marrocos Sampaio (2023)
The present study aimed to evaluate injectable mineral supplementation (IMS) in swine sows of different parity orders (PO) on reproductive performance, milk composition, and blood parameters, as well as on the performance and biochemical analysis of the blood of their litters. Sows (n=208) were selected and distributed in a 4 x 4 factorial completely randomized design consisting of four IMS groups and four groups of PO, totaling 16 treatments with 13 repetitions each. The sows were divided into four groups: 1st PO, 2nd PO, 3rd and 4th POs, and ≥5th PO. The supplementation groups were: CONCON – application of serum five days before artificial insemination (AI) and at 90 days of gestation; FOSCON – IMS 5 days before AI and application of serum at 90 days of gestation; CONFOS - application of serum five days before AI and IMS at 90 days of gestation; FOSFOS – IMS five days before AI and at 90 days of gestation. There was no interaction between IMS and PO on reproductive parameters or piglet performance. However, FOSFOS sows showed lower weight, percentage weight, and body protein losses than CONCON females. Sows ≥5th PO had higher weight at farrowing and weaning than other POs with lower weight and percentage losses than 1st PO sows. Females ≥5th PO also had greater backfat thickness at farrowing and weaning and body protein than 1st PO sows. On the other hand, the 2nd PO, and 3rd and 4th POs sows showed higher estimated milk production than the 1st and ≥5th PO sows. Females ≥5th PO had more piglets born than females from the 1st and 2nd POs. However, 1st PO sows had more piglets at weaning than ≥5th PO sows. Sows from the 3rd and 4th POs had higher litter and piglet weight at birth than those from the 1st PO. At weaning, sows of the 2nd PO and 3rd and 4th POs had higher litter and piglet weight compared to the 1st and ≥5th POs, with a similar response in litter and piglet weight gain. The composition of colostrum and sow milk did not change between supplementation or PO groups. Higher albumin values were observed for the three supplemented groups than for the CONCON group. The serum globulin level was higher in CONCON females than in the three supplemented groups. Glutathione peroxidase (GSH-PX) had higher levels in FOSFOS females, followed by CONFOS, while FOSCON sows did not differ from CONCON. Sows ≥5th PO had a higher concentration of total proteins than 1st PO females. GSH-PX was also superior in sows ≥5th PO, but only when compared to 2nd PO. In the breakdown of interactions within the supplementation groups, CONCON from 1st and ≥5th POs presented higher levels of thiobarbituric acid reactive species than sows from the 2nd to 4th POs. In the CONFOS treatment, superoxide dismutase (SOD) and catalase presented significantly lower levels in the ≥5th PO compared to the other parturition orders. In FOSCON sows, catalase was superior in the 2nd to 4th PO groups. There were no differences between POs within the FOSFOS treatment. Piglets from FOSFOS sows showed higher concentrations of GSH-PX than piglets from other sows. In turn, CONFOS piglets had higher serum GSH-PX values than FOSCON piglets, which was also higher than CONCON piglets. Lower serum TBARS values were found in FOSFOS piglets compared to CONCON and FOSCON, not differing from CONFOS. Piglets from 2nd PO sows had higher levels of hematocrit and monocytes than piglets from ≥5th PO sows, and piglets from 1st PO sows had lower total protein concentrations than those from ≥5th PO sows. In short, injectable mineral supplementation (P, Cu, K, Mg, and Se) in sows before artificial insemination and at 90 days of gestation has a beneficial effect, leading to lower maternal body losses during lactation and improving the serum antioxidant profile, regardless of the parity order, as well as the serum antioxidant profile of their litters.